PENGARUH MOTIVASI KERJA, KEPEMIMPINAN DAN EDISIPLINAN TERHADAP PRESTASI KERJA GURU SEKOLAH DASAR DI KABUPATEN PEMALANG - Peny Pratiwi; Sunandar Sunandar; Ghufron Abdullah (Jurnal Manajemen Pendidikan (JMP), 2016)
The purpose of this researh (1) Know and analyze the effect of work motivation on the teachers performance  (2) Determine and analyze the impact of school leadership on the teachers performance (3) Know and analyze the influence of discipline on the teachers performance and (4) Determine and analyze the effect of work motivation, school leadership and discipline on the teachers performance.The population in this study were all elementary school teachers in the area of State Sarwas I UPP Petarukan Pemalang of as much as 128 teachers, obtained a sample of 97 people by using proportional random sampling technique. The data collection method used was a questionnaire. Analysis of the data used is descriptive analysis, test validity and test hypotheses that include multiple linear regression analysis. Analyzing data using SPSS for windows Release 21.Based on the results of this research is that (1) There is significant influence teachers' motivation to work on the performance of elementary school teachers in the District Sarwas I Petarukan Pemalang, with a contribution of 40.1%; (2) There was a significant effect of school leadership on the performance of elementary school teachers in the District Sarwas I Petarukan Pemalang, with a contribution of 68.00%; (3) There is significant influence of discipline on the performance of elementary school teachers in the District Sarwas I Petarukan Pemalang, with a contribution of 48.8%; (4) There is significant influence work motivation of teachers, school leadership and discipline on the performance of elementary school teachers in the District Sarwas I Petarukan Pemalang, with a contribution of 83.3%.